Addressing the burden of premature birth and its prevention in developing countries: is it time to act now? - Singh Lakra, Mahaveer; Taksande, Amar; J. Meshram, Revat; Lakra, Ashwini; Kumar, Amit; Gandhi, Deepak; Prasad, Roshan; Wanjari, Mayur (Chulalongkorn Medical Journal, 2025)
India accounts for approximately 3.5 million preterm births annally, representing about 25% of the global burden. Premature birth poses a substantial burden, with an especially profound impact on families and health systems in low-and middle-income countries, where access to adequate healthcare is limited. Premature birth remains a leading cause of neonatal death among children under the age of five years due to organ immaturity, sepsis, and respiratory distress syndrome. Efforts to reduce premature birth include improving access to quality prenatal care, enhancing neonatal care services, and implementing targeted public health interventions. Despite ongoing challenges, considerable progress has been made through concerted efforts by governments, international organizations, healthcare providers, and community stakeholders. Continued investment, monitoring, and innovation are crucial to further prevent preterm births and improve the outcomes. Such efforts aim to alleviate the burden on families and caregivers while strengthening already strained health systems worldwide.